Collaborative funding of university research undertaking for rapid national development (2012)
The paper examined current level of collaborative funding of research undertakings in the Nigerian university system in order to determine the level to which various stakeholders (corporate and endowed individuals Nigerians) had been contributing their quote towards funding research in the university systems and to find out if research funding in the system matches the expected level of collaborative research funding. Two research questions were, therefore, addressed one hundred academics in the system from five Nigerian University who converged at a National Research Conference were used as sample and an instrument tagged Nigerian University Reseach Funding Perception Questionnaire was thus adminstered on the conferees from four of the six geo-political zones of the country. The data were analysed using graph and chi-square. Results were that collaborative funding apart from the ones jointly funded by government and the universities or government agency (e.g ETF) and universities, no meaningful collaborative funding of research in our universities, and that corporate bodies would fund sports and lottery/gambling because theses easily bring back quick return to them and that well-endowed individuals and corporate bodies should either voluntarily collaboratively fund research in the university system or a legislation should compel to undertake collaborative funding of research in university system for enhanced development of the country.In order to engender collaborative, the university system should evolve joint research initiating body that would be responsible for generating research policy, plans and programmes so that endowed individuals and the organized private sector could collaborate in funding the university system research understandings for rapid national development.